Imaging poliovirus entry in live cells. - Boerries Brandenburg; Lily Y Lee; Melike Lakadamyali; Michael J Rust; Xiaowei Zhuang; James M Hogle (PLoS Biology)
Viruses initiate infection by transferring their genetic material across a cellular membrane and into the appropriate compartment of the cell. The mechanisms by which animal viruses, especially nonenveloped viruses, deliver their genomes are only poorly understood. This is due in part to technical difficulties involved in direct visualization of viral gene delivery and to uncertainties in distinguishing productive and nonproductive pathways caused by the high particle-to-plaque forming unit ratio of most animal viruses. Here, we combine an imaging assay that simultaneously tracks the viral capsid and genome in live cells with an infectivity-based assay for RNA release to characterize the early events in the poliovirus (PV) infection. Effects on RNA genome delivery from inhibitors of cell trafficking pathways were probed systematically by both methods. Surprisingly, we observe that genome release by PV is highly efficient and rapid, and thus does not limit the overall infectivity or the infection rate. The results define a pathway in which PV binds to receptors on the cell surface and enters the cell by a clathrin-, caveolin-, flotillin-, and microtubule-independent, but tyrosine kinase- and actin-dependent, endocytic mechanism. Immediately after the internalization of the virus particle, genome release takes place from vesicles or tightly sealed membrane invaginations located within 100-200 nm of the plasma membrane. These results settle a long-lasting debate of whether PV directly breaks the plasma membrane barrier or relies on endocytosis to deliver its genome into the cell. We expect this imaging assay to be broadly applicable to the investigation of entry mechanisms for nonenveloped viruses.